America's Other Guantánamo: British Foreign Policy and the US Base on Diego Garcia. Issue 4 (17th July 2015) - Harris, Peter
Abstract: The British Indian Ocean Territory (BIOT) is one of Britain's most controversial Overseas Territories. Its indigenous people, the Chagossians, were exiled from their homes in the 1960s and 1970s so that BIOT could play host to a US military base on the island of Diego Garcia. Meanwhile, Diego Garcia has been tarnished by revelations regarding its role in the CIA's 'extraordinary rendition' programme and by allegations of torture. And earlier this year, an international tribunal ruled that the UK government had violated international law by pushing through a Marine Protected Area to cover the territory over and above the protestations of neighbouring states. In this article, I argue that allowing the resettlement of BIOT by the Chagossians would go a long way towards improving the way that the territory has been governed for the past five decades.